Correction to: Influence of Habesha eggshell on the dry sliding wear behavior of epoxy composites (Biomass Conversion and Biorefinery, (2024), 14, 17, (21523-21538), 10.1007/s13399-024-05482-9) - Shahapurkar K.; Ramesh S.; Nik-Ghazali N.-N.; Chenrayan V.; MC K.; Kanaginahal G.; Soudagar M.E.M.; Fouad Y.; M.A.Kalam (Springer Science and Business Media Deutschland GmbH, 2025)
In this article, the affiliation details for S. Ramesh were incorrectly given as ?Division of Research and Development, Lovely Professional University, 144411 Phagwara, Punjab, India? and ?Center of Advanced Manufacturing and Materials Processing (AMMP), Faculty of Engineering, University of Malaya, 50603 Kuala Lumpur, Malaysia? but should have been ?Institute of Power Engineering, Universiti Tenaga Nasional, 43000 Kajang, Selangor, Malaysia? and ?Center of Advanced Manufacturing and Materials Processing (AMMP), Faculty of Engineering, University of Malaya, 50603 Kuala Lumpur, Malaysia?. The original article has been corrected. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.